Self-Management as a Determinant in Reducing Gastritis Recurrence: A Chronic Care Model Approach - Selvia, Akub; Puguh K, Sri; Hatta, Candra; Musa'adah, Musa'adah (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2025)
Gastritis is one of the diseases of the digestive system with a high prevalence of recurrence. Irregular lifestyles, academic stress, and low self-management skills are the main factors that trigger relapse. The Chronic Care Model (CCM) has a conceptual framework in the management of chronic diseases including gastritis. This study aims to analyze factors related to gastritis recurrence based on the CCM approach in nursing students. This study used a cross-sectional quantitative design with a total of 30 respondents in young adulthood. The results showed that most of the respondents (86.7%) experienced a recurrence of gastritis in the last six months. The Fisher's Exact Test showed that the self-management support subscale had a significant relationship with gastritis recurrence (p = 0.048), while the other subscales (delivery system design, decision support, clinical information system, organization of care, and community resources) showed an insignificant association (p 0.05), but had a strong association in the high score category. The conclusion of this study shows that the higher the student's self-management ability, the lower the risk of gastritis recurrence.